Evaluation results of a 3D virtual environment for internet-accessible physics experiments - Scheucher, B.; Belcher, J.; Bailey, P.; dos Santos, F.; Guetl, Christian (International Association of Online Engineering, 2009)
In the science of physics the interrelation of physical theory, model and experiement is hard to comprehend, therefore group learning becomes more important. This fact, combined with the opportunity to work on practical experiences over distance in a collaboratively way, has raised worldwide the interest of creating new learning environments based on 3D virtual worlds.This paper outlines an evaluation that was performed to determine whether the addition of collaborative virtual learning environment (CVLE) to an internet-accessible physics experiment (iLab) would improve learning experience. We wanted to assess if the developed CLVE helps participants to achieve a better understanding of physics phenomena. Within this CLVE avatars represent learners and they are able to communicate and collaborate in a way similar to real life in order to perform physics experiments using the TEAL simulation toolkit. One of the major findings of this evaluation indicates that the reconsideration of design and additional items at the 3D visualization could further improve the learning process in the CLVE in a more effective way.